Curse of the Mummy-ji : The Influence of Mothers-in-Law on Women in India - Anukriti, S; Herrera-Almanza, Catalina; Pathak, Praveen K.; Karra, Mahesh (John Wiley and Sons, 2022)
Restrictive social norms and strategic constraints imposed by family members can limit women's access to and benefits from social networks, especially in patrilocal societies. We characterize young married women's social networks in rural India and analyze how inter-generational power dynamics within the household affect their network formation. Using primary data from Uttar Pradesh, we show that co-residence with the mother-in-law is negatively correlated with her daughter-in-law's mobility and ability to form social connections outside the household, especially those related to health, fertility, and family planning. Our findings suggest that the mother-in-law's restrictive behavior is potentially driven by the misalignment of fertility preferences between the mother-in-law and the daughter-in-law. The lack of peers outside the household lowers the daughter-in-law's likelihood of visiting a family planning clinic and of using modern contraception. We find suggestive evidence that this is because outside peers (a) positively influence daughter-in-law's beliefs about the social acceptability of family planning and (b) enable the daughter-in-law to overcome mobility constraints by accompanying her to health clinics. Wiley Terms and Conditions, https://authorservices.wiley.com/author-resources/Journal-Authors/licensing/self-archiving.html